Shock wave characterization of precipitate strengthening of PH 13–8 Mo stainless steel. (1st April 2020) - Hillel, G.; Meshi, L.; Kalabukhov, S.; Frage, N.; Zaretsky, E.B.
Abstract: The shear stresses required for dislocations passage of highly coherent NiAl-based precipitates, formed in commercial PH 13–8 Mo steel after homogenization, quenching and aging for different duration of time at 510 °C, were determined in a series of planar impact experiments using samples with different thickness. The experiments revealed two regimes of decay of the elastic precursor waves: a fast one, at the shear stress τ greater than some threshold τ *, associated with the interaction of moving dislocations with lattice phonons, and a slow one, at τ < τ *, corresponding to the precipitates' cutting with the help of thermal fluctuations. Consequently, the stress τ * can be regarded as the stress which permits the passage of the precipitate by a dislocation without thermal support. Precipitates' geometry and size, determined based on the activation volume at thermally-activated regime, are in a reasonable agreement with precipitates dimensions estimated from High Resolution Transmission Electron Microscopy images. Graphical abstract: Image, graphical abstract